Makna Kasih Tuhan bagi Bangsa Israel Melalui Peristiwa Hosea Mengawini Gomer yang Terdapat di dalam Kitab Hosea 1:2-9 - Zebua, Boyman Aspirasi; Hatlan, Ruby (Jurnal Shema, 2023)
This article discusses the picture of God's love for Israel through the marriage of Hosea and Gomer. However, the relationship between the husband and wife was not like that of a husband and wife who expect to live happily, love each other, and even complement each other. Instead, it was the depravity of the Israelites. Even more fatally, the background problem in this article is that there are still many Christians who disagree with what God did to the Israelites. Even though God's power is evident to that person, the individual still hardens his or her heart to disagree with God's actions, because to them, the God they know is a God of love, not a God who is angry with His creation. Therefore, it is important to understand God's love for the Israelites through the marriage metaphor between Hosea and Gomer. This study aims to discuss the theological overview of the Book of Hosea about Hosea marrying Gomer and the love of God in it. The writing method used in writing this article is Qualitative in the form of words with a literature review of various literature sources related to the topic under study. The results show that the Book of Hosea has used the metaphor of Hosea's marriage to Gomer, which is to show the social chaos that occurred, where the Israelites had been unfaithful to God, but God still loved the Israelites.